2003
DOI: 10.1086/379677
|View full text |Cite
|
Sign up to set email alerts
|

WIYN Open Cluster Study. XVII. Astrometry and Membership toV=21 in NGC 188

Abstract: We present techniques for obtaining precision astrometry using old photographic plates from assorted largeaperture reflectors in combination with recent CCD Mosaic Imager frames. At the core of this approach is a transformation of plate/CCD coordinates into a previously constructed astrometric reference frame around the open cluster NGC 188. This allows us to calibrate independently the optical field angle distortion for all telescopes and field correctors used in this study. Particular attention is paid to co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
153
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(160 citation statements)
references
References 27 publications
7
153
0
Order By: Relevance
“…For example one could use the spectroscopic binary properties which Geller & Mathieu (2011) found for NGC 188 instead of the solar-type field binary properties. Furthermore one could set the probability for a star to be a cluster member f c to the membership probabilities derived from the proper motion analysis of Platais et al (2003). Finally one could use a model for the Milky Way (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example one could use the spectroscopic binary properties which Geller & Mathieu (2011) found for NGC 188 instead of the solar-type field binary properties. Furthermore one could set the probability for a star to be a cluster member f c to the membership probabilities derived from the proper motion analysis of Platais et al (2003). Finally one could use a model for the Milky Way (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…5. The literature values for these parameters, derived from a proper motion analysis (Platais et al 2003) and the multi-epoch radial velocity data (Geller et al 2008;Geller & Mathieu 2011) have been plotted as black dots. If the error bars are given, they have been plotted.…”
Section: Case Study: Ngc 188mentioning
confidence: 99%
“…A number of excellent studies have previously been performed for NGC 188 that have accurately determined its physical parameters (von Hippel & Sarajedini 1998;Sarajedini et al 1999;Platais et al 2003;Michaud et al 2004;Stetson et al 2004;. NGC 188 is used as a fiducial cluster, and a precise age is obtained for Berkeley 17 relative to NGC 188.…”
Section: Introductionmentioning
confidence: 99%
“…As the highest priority cluster in the WIYN Open Cluster Study, excellent, multicolor color-magnitude diagrams (CMDs) and proper-motion data have been published for this cluster (von Hippel & Sarajedini 1998;Sarajedini et al 1999;Platais et al 2003). In their UBVRI photometric study, Sarajedini et al (1999) found that NGC 188 has an age of 7:0 AE 0:5 Gyr, a reddening of E(B À V ) ¼ 0:09 AE 0:02, and a distance modulus of (m À M ) V ¼ 11:44 AE 0:08.…”
Section: Introductionmentioning
confidence: 99%
“…NGC 188 is one of the oldest known open clusters of the Milky Way belonging to the old Galactic disk population (Platais et al 2003). The cluster's spatial location in the Galaxy (l = 122…”
Section: Introductionmentioning
confidence: 99%